2018
DOI: 10.1007/s12035-018-1292-5
|View full text |Cite
|
Sign up to set email alerts
|

An Antagonistic Axon-Dendrite Interplay Enables Efficient Neuronal Repair in the Adult Zebrafish Central Nervous System

Abstract: Neural insults and neurodegenerative diseases typically result in permanent functional deficits, making the identification of novel pro-regenerative molecules and mechanisms a primary research topic. Nowadays, neuroregenerative research largely focuses on improving axonal regrowth, leaving the regenerative properties of dendrites largely unstudied. Moreover, whereas developmental studies indicate a strict temporal separation of axogenesis and dendritogenesis and thus suggest a potential interdependency of axon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
30
0
8

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(41 citation statements)
references
References 73 publications
1
30
0
8
Order By: Relevance
“…Therefore, it is meaningful to explore the approaches to promote axonal regeneration after. Recently, various neuroregenerative researches have focused on dendritic and axonal repair to improve functional recovery after CNS injury [51]. Previous studies have shown that metformin exerts neuroprotective effect and promotes functional recovery of memory deficits via anti-inflammation and triggering neurogenesis [52].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, it is meaningful to explore the approaches to promote axonal regeneration after. Recently, various neuroregenerative researches have focused on dendritic and axonal repair to improve functional recovery after CNS injury [51]. Previous studies have shown that metformin exerts neuroprotective effect and promotes functional recovery of memory deficits via anti-inflammation and triggering neurogenesis [52].…”
Section: Discussionmentioning
confidence: 99%
“…Dendrites can experience damage during traumatic brain injury (TBI) [8][9][10], and dendrite degeneration has been observed in neurodegenerative disease [11][12][13]. It has also been shown that dendrites simplify after axon damage [14][15][16][17]. In the case of retraction after axon injury, dendrites can re-elaborate if the axon reaches a target [15].…”
Section: Introductionmentioning
confidence: 99%
“…It has also been shown that dendrites simplify after axon damage [14][15][16][17]. In the case of retraction after axon injury, dendrites can re-elaborate if the axon reaches a target [15]. In vertebrate models, it has not been determined whether neurons can recover arbors after direct dendrite damage.…”
Section: Introductionmentioning
confidence: 99%
“…We hypothesized that regeneration-associated gene expression changes in axotomized RGCs would follow a temporal pattern corresponding to the changing requirements of axons as they grow through different environments leading from retina to optic tectum. The timing of successful axon regeneration after optic nerve crush in zebrafish is well characterized (7,8,20). To achieve a comprehensive picture of the genetic programming driving successful vertebrate CNS axon regeneration, we used RNA-seq to identify changes in gene expression that accompanied axon growth in regenerating RGCs at critical time points after optic nerve injury.…”
Section: Stage-specific Temporal Changes In Regeneration-associated Gmentioning
confidence: 99%
“…We specifically examined how transcript expression in naĂŻve retinas compared with that in retinas dissected from fish at 2, 4, 7, and 12 days post-injury (dpi). Based on the previously established regeneration chronologies, our chosen time-points correspond to following stages of optic nerve regeneration: (a) axon growth past the site of injury toward the midline, (b) axon guidance across the midline, (c) selection of axon targets within the brain, and (d) synaptogenesis in the optic tectum ( (7,8,20); Fig. 1A).…”
Section: Stage-specific Temporal Changes In Regeneration-associated Gmentioning
confidence: 99%